Analisis Quantitative Strategic Planning Matrix (QSPM) dan Perumusan Strategi Bisnis Berbasis Business Model Canvas pada Apotek Permata Pondok Gede - Rosiyana, Rosiyana; Kosasih, Kosasih; Wirabarata, IgedeMade (PENDIPA Journal of Science Education, 2025)
This study aimed to analyze and formulate new business strategies to optimize the performance of Apotek Permata Pondok Gede using the Quantitative Strategic Planning Matrix (QSPM) and Busniness Model Canvas (BMC) approaches. An exploratory quantitative method was employed, incorporating internal and external strategic analyses through tools such as SWOT, IFE, EFE, IE Matrix, Grand Strategy Matrix, and TOWS analysis. These findings were integrated into the QSPM framework to prioritize strategic alternatives and mapped onto the nine elements of the BMC to design an adaptive business model. Data were collected through interviews, observation, documentation, and triangulation. The analysis identified six priority components within the BMC-Customer Relationships, Value Propositions, Channels, Revenue Streams, Key Activities, and Key Resources-as critical to the pharmacy’s strategic development. The QSPM results indicated that forming strategic patnerships with technology providers to support the implementation of the PSEF (Electronic System for Pharmaceutical Services) and integrate it with the pharmacy’s operations yielded the highest Total Attractiveness Score (TAS) of 6.19, making it the top strategic priority.